Highly Efficient and Tunable Spin-To-Charge Conversion Through Rashba Coupling at Oxide Interfaces - Oyarzun-Medina, S (Nature Publishing Group, 2016)
The spin-orbit interaction couples the electrons motion to their spin. As a result, a charge current running through a material with strong spin-orbit coupling generates a transverse spin current (spin Hall effect, SHE) and vice versa (inverse spin Hall effect, ISHE). The emergence of SHE and ISHE as charge-to-spin interconversion mechanisms offers a variety of novel spintronic functionalities and devices, some of which do not require any ferromagnetic material. However, the interconversion efficiency of SHE and ISHE (spin Hall angle) is a bulk property that rarely exceeds ten percent, and does not take advantage of interfacial and low-dimensional effects otherwise ubiquitous in spintronic hetero-and mesostructures. Here, we make use of an interface-driven spin-orbit coupling mechanism-the Rashba effect-in the oxide two-dimensional electron system (2DES) LaAlO3/SrTiO3 to achieve spin-to-charge conversion with unprecedented efficiency. Through spin pumping, we inject a spin current from a NiFe film into the oxide 2DES and detect the resulting charge current, which can be strongly modulated by a gate voltage. We discuss the amplitude of the effect and its gate dependence on the basis of the electronic structure of the 2DES and highlight the importance of a long scattering time to achieve efficient spin-to-charge interconversion. © 2016 Macmillan Publishers Limited. All rights reserved.